2015
DOI: 10.1002/jcsm.12068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of C-terminal Agrin Fragment as a marker of muscle wasting in patients after acute stroke during early rehabilitation

Abstract: BackgroundC‐terminal Agrin Fragment (CAF) has been proposed as a novel biomarker for sarcopenia originating from the degeneration of the neuromuscular junctions. In patients with stroke muscle wasting is a common observation that predicts functional outcome. We aimed to evaluate agrin sub‐fragment CAF22 as a marker of decreased muscle mass and physical performance in the early phase after acute stroke.MethodsPatients with acute ischaemic or haemorrhagic stroke (n = 123, mean age 70 ± 11 y, body mass index BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 50 publications
5
64
2
Order By: Relevance
“…This finding reinforces the notion that a low PA is associated with sarcopenia, a key biological substrate of the frailty syndrome that results from accelerated age‐related loss of skeletal muscle mass and strength 31. PA has previously been shown to correlate with biomarkers of muscle degeneration32 and to decrease after muscle injury,33, 34, 35 supporting the biological plausibility of a link between decreased PA and not only low muscle mass, but also impaired muscle function. More important, the addition of low PA to risk models that included the SPPB demonstrated incremental prognostic value, highlighting the complementary relationship between PA and existing frailty scales.…”
Section: Discussionsupporting
confidence: 83%
“…This finding reinforces the notion that a low PA is associated with sarcopenia, a key biological substrate of the frailty syndrome that results from accelerated age‐related loss of skeletal muscle mass and strength 31. PA has previously been shown to correlate with biomarkers of muscle degeneration32 and to decrease after muscle injury,33, 34, 35 supporting the biological plausibility of a link between decreased PA and not only low muscle mass, but also impaired muscle function. More important, the addition of low PA to risk models that included the SPPB demonstrated incremental prognostic value, highlighting the complementary relationship between PA and existing frailty scales.…”
Section: Discussionsupporting
confidence: 83%
“…36 Cheung et al recently reported that testosterone deprivation selectively decreases lower limb muscle function, predominantly affecting muscles that support body weight and muscles that accelerate the body forward during walking and mediate balance. 51 Sensitivity and specificity 1076 Editorial of biomarkers such as C-terminal agrin fragment and other such candidates remain however unsatisfying. 37,38 Anorexia, on the other hand, plays also a major role in the pathogenesis of wasting in both sarcopenia and cachexia.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%
“…[46][47][48][49] An interesting candidate biomarker Cterminal agrin fragment has been used in patients with HF 50 and in patients after acute stroke. 51 Sensitivity and specificity 1076 Editorial of biomarkers such as C-terminal agrin fragment and other such candidates remain however unsatisfying. 52 Another interesting approach is the assessment of handgrip strength using a handgrip dynamometer.…”
Section: Screening and Diagnosing Sarcopeniamentioning
confidence: 99%
“…[17][18][19][20][21] Several other circulating factors like GDF-15, 22 activin A, 23 and low testosterone 24 have been associated with muscle loss and survival in sarcopenia and cachexia and therefore can be considered potential biomarkers, but need to be validated in large trials. 1 This is of particular importance in muscle wasting, as there are very few blood-based biomarkers such as myostatin or agrinin that correlated with muscle mass.…”
Section: Introductionmentioning
confidence: 99%